Addressing Tobacco in Managed Care: Results of the 2002 Survey - Carol McPhillips-Tangum; Carmella Bocchino; Rita Carreon; Caroline Erceg; Bob Rehm (Centers for Disease Control and Prevention, 2004)
Introduction In the United States, tobacco use is the leading preventable cause of death and disease. The health and cost consequences of tobacco dependence have made treatment and prevention of tobacco use a key priority among multiple stakeholders, including health plans, insurers, providers, employers, and policymakers. In 2002, the third survey of tobacco control practices and policies in health plans was conducted by Americas Health Insurance Plans technical assistance office as part of the Addressing Tobacco in Managed Care (ATMC) program. Methods The ATMC survey was conducted in the spring of 2002 via mail, e-mail, and fax. A 19-item survey instrument was developed and pilot-tested. Of the 19 items, 12 were the same as in previous years, four were modified to collect more detailed data on areas of key interest, and three were added to gain information about strategies to promote smoking cessation. The sample for the survey was drawn from the 687 plans listed in the national directory of member and nonmember health plans in America's Health Insurance Plans. Results Of the 246 plans in the sample, 152 plans (62%) representing more than 43.5 million health maintenance organization members completed the survey. Results show that health plans are using evidence-based programs and clinical guidelines to address tobacco use. Compared to ATMC survey data collected in 1997 and 2000, the 2002 ATMC survey results indicate that more health plans are providing full coverage for first-line pharmacotherapies and telephone counseling for smoking cessation. Plans have also shown improvement in their ability to identify at least some members who smoke. Similarly, a greater percentage of plans are employing strategies to address smoking cessation during the postpartum period to prevent smoking relapse and during pediatric visits to reduce or eliminate childrens exposure to environmental tobacco smoke. Conclusion The results of the 2002 ATMC survey reflect both tremendous accomplishments and important opportunities for health plans to collaborate in tobacco control efforts. With appropriate support, analytical tools, and resources, it is likely that health plans, clinicians, providers, and consumers will continue to evolve in their efforts to reduce the negative consequences of tobacco use.